Le mobilier en cuir antique et médiéval du boulevard Dr Henri-Henrot à Reims/Durocortorum - Martine Leguilloux (Gallia)
This article gathers the main conclusions of a study on leather working analysis based on 1,702 leather fragments, i.e. 642 objects (minimum number of objects: MNO), discovered on the ZAC du Vieux-Port site, located on boulevard Dr. Henri-Henrot in Reims (Marne). Three main categories were identified: 1% of the pieces (MNO) are accessories (belts, lanyards), 23.70% are crafting scraps and 75.30% are footwear components, representing a large collection of ancient models, dated between the end of the 1st and the beginning of the 2nd c., as well as the end of the 4th and beginning of the 5th c. (states 7 to 11). More modestly, there are some artifacts from the medieval period, dated to the second half of the 14th c. and the middle of the 15th c. (states 12 and 13). The categories of footwear in this study were classified according to their design model: closed models designed with several elements (quarters) attached to the sole; the sandals, and shoes without straps or attachments, like a mule or a clog. For each group, we have endeavored to detail the principal relevant technical information: stitching types, manufacturing of applied decorations, elaboration and characteristics of stud and nail arrangements. We have also attempted to highlight the primary cultural or gender distinctions, as well as propose a differential chronology based on form. For closed shoes, the generic term calceus will be used in this article to designate them, a denomination that can be found throughout the Roman period until late Antiquity and which may be applied to several different models. For convenience, it will also be used for medieval footwear, pending an exhaustive study on relevant shoe names for the 14th and 15th c. The main components preserved in this category of material culture are the upper portions of the shoe (quarters and reinforcements) and the soles. The fragments of the upper portions represent only 5.50% of the elements identified (MNO) and are often too partial to allow for a complete reconstruction of the shoe. Nevertheless, a few pieces from Antiquity excavation levels allow for a simple classification into two large groups: the first is that of the integral uppers, of sufficient dimension to allow for the total envelopment of the foot, attested to in states 8 and 9 (between the middle of the 2nd c. and the end of the 3rd c.). The second group is that of the quartered upper portions, which are found in all levels until the early Middle Ages (state 13). For each group, high topped models exist, rising to the ankle, and others with lower upper portions. Of the isolated pieces, 11.30% are small elements of reinforcement, positioned at points sensitive to wear, for example at the junction between the vamp and the sole. Heel reinforcements are the most abundant, rectangular in shape with a slightly convex arc along the upper edge, their base was fixed to the soles by nail stems. Upper reinforcements are smaller in size, and sewn to the front ends, on the external faces. The soles represent 85% of the identified fragments. The most frequent assembly pattern is a superposition of three independent soles: the outsole in contact with the ground, the midsole or comfort sole and the insole in contact with the foot. For 18.40% of the calcei insoles in states 8 and 9, the comfort insoles were replaced by a composite midsole (CIS): a superposition of small leather elements in the space between the outsole and the insole establishing significant thickness (2 cm) and improved walking comfort. Two types of composite insoles have been identified, the first (SIC 1) is a superposition of half soles and well-shaped heel pieces; the second (SIC 2) is an accumulation of heterogeneous fragments, of various shapes and sizes, roughly cut, whose appearance is similar to shoemaking scraps. Nailing of the soles was systematic for Antiquity level calcei (states 8 to 10), 165 complete or partially preserved soles have been reconstructed with their nail arrangements. Later period soles, from states 11 to 13, bear no trace of nail insertion. For most of the nail-bearing soles, knowledge of their placement represents an opportunity to reproduce decorative motifs. They have been classified into four main types according to their assumed forms and degree of complexity. Some patterns are recurrent, depending on the size and shape of the soles, suggesting an adjustment of decoration according to shoe use, and the gender or age of the wearer. Sandals represent 8.40% of the shoes identified in states 8 to 10. The models are categorized by the shape of the soles: those with a rounded cut in the front, those with an anatomical cut, taking on the shape of one or more toes and finally, those with a very flared shape in the front portion of the shoe, at toe level, presenting a rectilinear cut. Most of the sandals have decorated soles (20 soles out of 29 pieces identified): the surface in contact with the foot presents patterns of palmettes or eyespots (ocelles), applied by pressure with stamping machines. These motifs are sometimes isolated, but are often composite, and can be found on pieces of all sizes, including children’s sandals. The soles of the sandals are almost always studded with very simple motifs: a few triangles and diamond shapes on sandals of states 8 and 9, a simple peripheral studding on the soles of state 10. The foot ties have almost entirely disappeared, a few traces on the soles allow us to restore the layout and form of axial straps fixed with loops at the front, that would have risen and passed between the toes; some models were fitted with transverse front straps, fixed on either side of the sole. Other models of Sculponeae style (mules and clogs) footwear are absent from this material, such as the one with raised edges and a network of straps usually referred to as “carbatina”, but others, rarer, are present, as is the case for “mules” (wherein the foot is free in the rear portion of the shoe, but entirely covered in the front), as well as shoes with cork soles. Two fragments of upper portions were retrieved among the material culture from the states 8 and 9. These were made from the skin of a small ruminant and presented a characteristic butterfly wing cut-out. A vamp fragment has, on one of its intact edges, marks of nail insertion intended to fix it to the edge of the sole, a configuration indicating the use of wooden or cork soles. A fragment of a nailed cork sole was also part of the ancient material culture and might correspond to this very particular model of shoe.